The imp of the reverse: A phenomenology of the unconscious - Gruba-McCallister, Frank P. (Journal of religion and health, 1993)
The debate regarding the unitary versus multiple nature of the human person is examined with special attention to the division between conscious and unconscious. The roots of the unconscious are traced to the experience of alienation or feeling divided within. An existential analysis is provided in order to shed light on the nature of the unconscious. The experience of feeling divided within is explained as a metaphor that is taken literally. An existential-phenomenological explanation of the unconscious is provided which preserves the essential unity of the human person.